The Challenges of Talent Drain in Northeast China and Urban Planning Response Strategies - Ziwei Wei (Journal of Frontier in Economic and Management Research, 2025)
The report of the 20th National Congress of the Communist Party of China points out that "talents are the primary resource", and the quantity and quality of talents are important factors determining the competitiveness of a city. In recent years, the problem of talent outflow in Northeast China has been severe, which has to some extent affected the optimization of the industrial structure and economic and social development in Northeast China. This paper analyzes the reasons for the outflow of talents in Northeast China and, on this basis, puts forward relevant countermeasures and suggestions for urban planning in Northeast China, hoping to play a certain reference role in solving the problem of talent outflow in Northeast China.